Feature Papers in Mathematical and Computational Applications - Rozza, Gianluigi; Schütze, Oliver; Fantuzzi, Nicholas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume comprises the first collection of papers submitted by the Editorial Board Members (EBMs) of the journal Mathematical and Computational Applications (MCA), as well as outstanding scholars working in the core research fields of MCA. This collection typifies the most insightful and influential original articles regarding key topics in these fields.